DIURNAL RHYTHM AND SALT RESPONSIVE RESHAPING OF GUT MICROBIOTA CORRELATES WITH HYPERTENSION. (April 2021) - Chakraborty, Juthika Mandal Saroj; Cheng, Xi; Galla, Sarah; Hindupur, Anay; Saha, Piu; Yeoh, Bang San; Mell, Blair; Yeo, Ji -Youn; Vijay-Kumar, Matam; Yang, Tao; Joe, Bina
Abstract : Objective: Aberrant diurnal rhythms of Blood Pressure (BP) are well known to be associated with hypertension, however, whether rhythmicity of microbiotal composition is associated with salt sensitive hypertension remains unknown. We hypothesized that BP and gut microbiotal composition follow synchronous rhythms in high salt fed Dahl Salt Salt-Sensitive (S) rats and contribute to the progression of hypertension. Design and method: To test this hypothesis, we examined groups of Dahl S rats for their diurnal rhythms of both the gut microbiota and blood pressure in low salt (0.3%) and high salt (2%) conditions. Results: In high salt fed animals, Firmicutes/Bacteroidetes (F/B) ratio significantly changed between the dark (active) and light (rest) phases, which correlated with the diurnal rhythmicity of BP suggesting salt mediated rhythmic regulation of microbiota. Diurnal rhythms of Firmicutes, Bacteroidetes and Actinobacteria were independently associated with BP and significant in high salt fed animals. Discrete genera were observed to correlate independently or interactively with one or more of the following 3 factors- 1) BP rhythm, 2) dietary salt, 3) amplitude of BP. Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUST) analysis revealed diurnal rhythmicity of microbiotal pathways. During the active phase of the host, microbiota upregulated biosynthetic processes whereas during the resting phase of the host, microbiota upregulated degradation pathways of metabolites. These diurnal changes in microbiota, their functional pathways and BP response were prominently associated with a concerted rhythmicity of renal Lipocalin 2 and Endothelin1. Conclusions: Collectively, these data demonstrated the existence of synchronous diurnal rhythms of BP and renal inflammation with diurnal reshaping of gut microbiota in salt-sensitive hypertension. Such a concerted rhythmicity with peaks observed at the mid-active phase suggests that targeting this timepoint to reshape microbiota and/or intervene with medication could benefit hypertensives.